The Effect of Education, Income, Unemployment, and Poverty toward the Gini Ratio in Member of OIC Countries - Hasna Fauziana; Akhmad Kusuma Wardhana; Sulistya Rusgianto (Lembaga Penelitian dan Pengembangan Teknologi dan Rekayasa, Yayasan Ahmar Cendekia Indonesia, 2022)
This study aims to observe the effect of the Gini Ratio with factors of education, income, unemployment, and poverty in OIC member countries. This study uses purposive sampling in collecting data in the form of 24 OIC countries between 2010-2019. The data were observed using a random effect model after the Chow and Iju Hausman tests were carried out. The results show that only poverty has a significant effect on the Gini ratio. Poverty which is certainly caused by inequality in income received against expenditure causes a serious increase in poverty which in turn affects the Gini index number. Factors such as income, primary school education, and unemployment have no significant effect on the Gini ratio.